1983
DOI: 10.1159/000206875
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Levels, Opsonic Activity and Phagocytic Power in Egyptian Thalassemic Children

Abstract: Serum IgG, IgM and IgA were determined in 25 patients with homozygous beta thalassemia and 7 with the trait. The levels were increased in homozygous patients and increased further after splenectomy. Serum opsonic activity against Salmonella typhi and staphylococci was impaired in homozygous patients. Splenectomy caused more impairment against salmonella only. Similarly, phagocytic power against both organisms was lower in beta thalassemia. Further decrease against salmonella occurred after splenectomy. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
2
3
1
Order By: Relevance
“…It has been attributed to viral stimulation or cell transformation by known or unknown agents. The intensive polyclonal B-cell activation found in vivo in thalassemia is in accordance with elevated levels of serum immunoglobulins reported in this disease [21]. Although the number of spontaneous PFC was elevated in thalassemic patients, their lymphocytes when induced by PWM differentiated to immunoglobulin-secreting cells in a lesser number than in the controls.…”
Section: Discussionsupporting
confidence: 85%
“…It has been attributed to viral stimulation or cell transformation by known or unknown agents. The intensive polyclonal B-cell activation found in vivo in thalassemia is in accordance with elevated levels of serum immunoglobulins reported in this disease [21]. Although the number of spontaneous PFC was elevated in thalassemic patients, their lymphocytes when induced by PWM differentiated to immunoglobulin-secreting cells in a lesser number than in the controls.…”
Section: Discussionsupporting
confidence: 85%
“…The hypergammaglobulinemia en countered in these patients can be explained partly by the increased help provided by T helper cells to B lymphocytes and partly by the hyperplasia of the reti culoendothelial system which was reported by Khal ifa et al [4]. Delayed cutaneous hypersensitivity reac tions and the ability to release the MIF were found to be the same in beta-thalassemia major trait and in normal controls.…”
Section: Discussionsupporting
confidence: 56%
“…Splenectomized individ uals under 3 years of age are liable to die from septi cemia, specially due to encapsulated organisms [3]. In order to clarify factors making thalassemic patients more susceptible to infections, Khalifa et al [4] stud ied immunoglobulin levels, opsonizing activity and phagocytic power and the effect of splenectomy on them in patients with thalassemia. They reported in creased serum immunoglobulins (IgG, IgM and IgA).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have confirmed the findings about disruption of the functional activity of PMN. A study conducted in 25 patients with β-thalassemia major from Egypt has shown a decrease in phagocytic index to both salmonella and staphylococcus in patients [10]. Also found a disruption of chemotaxis and spontaneous migration of PMN in β-thalassemia major [11,12].…”
Section: Introductionmentioning
confidence: 99%